Implementasi Sensor Optik Berbasis IoT untuk Pemantauan Real-Time pada Proses Pengolahan Minyak Sawit - Fakhruddin; Wahyu Priayanto (Jurnal Inotera, 2024)
Optical sensors are widely used in various industrial sectors, including petrochemical and medical industries, with applications ranging from oxygen level measurement, concentration of substances in a liquid, object detection, and more. Optical sensors can be used to detect the water content in oil, such as palm oil or other oils. In an industrial process, especially in the palm oil industry, the water content in oil must meet a maximum standard of 4.5%. Optical sensors can measure water content using various methods, such as Total Internal Reflection (TIR) or Mid-Infrared (MIR), and can be monitored in real-time using IoT-based applications. The utilization of sensitive optical technology takes advantage of changes in the refractive index caused by variations in water content in palm oil. The method employed involves the development of an optical sensor based on the Mid-Infrared principle, which measures the amount of light absorbed by water and the light reaching the sensor for comparison. The results of water content measurements in palm oil that have been conducted can only be implemented for water content measurements of 0-5% in palm oil, with a sensor response that is less than linear above 5% water content. By correcting the non-linearity error of the sensor, the data is reduced to produce measurement results that are closer to the actual water content in palm oil, which will be displayed on local monitoring and real-time or continuous monitoring through IoT using smartphones and PCs wirelessly via IoT-based applications